Acanthocorticium brueggemannii, a new corticioid genus and species related to cyphelloid fungi in the euagarics clade (Agaricales, Basidiomycota) - Baltazar, Juliano M. (2015)
Acanthocorticium brueggemannii gen. et sp. nov. is introduced based on specimens from Southern Brazil. This corticioid fungus is characterized by resupinate basidiomes with smooth to tuberculate hymenophore, a monomitic hyphal system with simple-septate hyphae, finely echinulate halocystidia, cylindrical to clavate, dextrinoid acanthophyses, and globose, hyaline, smooth, and thin-walled IKI– basidiospores. Phylogenetic analyses of a LSU data set and a combined data set of ITS and LSU were carried out and the new taxon was found to be related to cyphelloid fungi within the Agaricales. Descriptions and drawings of the microscopic features of A. brueggemannii are provided.